Assessment Knowledge and Attitudes of the Family Physicians Towards Homeopathy: A Cross-Sectional Research - Ilhan, Fulya; Kurt, Osman; Oguzoncul, Ayse Ferdane (My University, 2021)
Objective: This study aimed to evaluate the knowledge\rand attitudes of homeopathy among family physicians. Material and\rMethods: Family physicians in Elazığ formed the universe of this\rcross-sectional study. We aimed to attain the whole universe without\rselecting any sample. The questionnaire used in the study includes 3\rstages, inquiring about sociodemographic characteristics, the attitude\rof homeopathy, and the homeopathy-related information. Twenty-one\rquestions were asked for information questions. One point was received for the correct answer to each item. Results: The median age of\rthe family physicians was 43.33 (33.0-49.0) years. Of these physicians, 65.6% were male, 34.4% were female; also, only 14.6% participated in any course, training, or certificate program related to\rhomeopathy. Although 66.0 % of the study participants wanted to receive a training/course about homeopathy as an alternative treatment\rmethod, 55.3% wanted a homeopathy department to be constructed in\runiversities. We found the knowledge of the family physicians who attended to any course/training/certificate program in homeopathy to be\rsignificantly higher than those who did not. There was a statistically\rsignificant difference between the knowledge scores and the answers\rgiven to the questions listed below: “Would you like to receive a course/training about the homeopathy method?”, “Would you like a homeopathy department to be constructed in universities?” and “Would\ryou think homeopathy is beneficial?”. This difference resulted from the\ranswers received as ‘yes’ and ‘undecided, in all three questions. Conclusion: As a result, according to our study findings, more than half of\rthe study participants want to receive training about homeopathy as an\ralternative treatment method, and want a homeopathy department to be\rconstructed in universities. We, therefore, recommend educating physicians about homeopathy and to be built up homeopathy departments in\rmedical faculties to increase the knowledge and awareness of this issue.
Keywords: Tamamlayıcı ve Entegre Tıp